2010
DOI: 10.1002/ccd.22593
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of the lost and found right coronary artery

Abstract: Most coronary artery anomalies are discovered only incidentally during coronary angiography. Recognition and identification of these anomalies especially during coronary intervention procedures are of importance because of their occasional association with symptoms due to atherosclerotic coronary disease. Anomalous origin of the right coronary artery (RCA) from the left anterior descending coronary artery (LAD) is one of the most uncommon coronary anomalies. We report an extremely interesting case of anomalous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Some challenges for the operator are the anatomy of AORCA (location and configuration of the ostium, immediate take off angle, lesion location and tortuosity of the vessel) and the diameter of the aortic root. [17][18][19] A retrospective study of elective cases by Uthayakumaran, et al, 8 showed that the average number of guide catheters used for a single PCI of AORCA was three or more, which indicates the challenges involved in the intervention of AORCA. In our study, four guides were consecutively attempted to cannulate the AORCA in a case at the beginning of a study, and in another case with subclavian tortuosity; subsequently the number of guides required gradually diminished with increasing experience in such cases of RCA-LSV.…”
Section: Discussionmentioning
confidence: 99%
“…Some challenges for the operator are the anatomy of AORCA (location and configuration of the ostium, immediate take off angle, lesion location and tortuosity of the vessel) and the diameter of the aortic root. [17][18][19] A retrospective study of elective cases by Uthayakumaran, et al, 8 showed that the average number of guide catheters used for a single PCI of AORCA was three or more, which indicates the challenges involved in the intervention of AORCA. In our study, four guides were consecutively attempted to cannulate the AORCA in a case at the beginning of a study, and in another case with subclavian tortuosity; subsequently the number of guides required gradually diminished with increasing experience in such cases of RCA-LSV.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of anomalous RCA has been reported to be the highest in the Indian subcontinent 3. Anomalous RCA after originating from the left system often courses along the anterior wall of the right ventricle or sometimes it courses between the pulmonary trunk and ascending aorta where its compression can lead to arrhythmias and sudden death and is also prone for atherosclerosis due to tortuosity.…”
Section: Descriptionmentioning
confidence: 99%